TRAVEL, GRIEF AND FIGHT: COMPUTATIONAL TRACING OF FEMALE WORKS IN THE DUTCH EAST INDIES LITERATURE - Astari, Amalia Putri (International Review of Humanities Studies, 2021)
In the canon of the Dutch Indies literature, the works of female writers are sometimes overlooked. Mainly when it appears in the early period of the Dutch colonial period, the central issue and genre in most of the literary works are frequently written by male authors through a masculine colonial perspective. This paper explores the works of female authors in the period of the Dutch East Indies (1800-1942) using two computational tools. The aim is to examine the most common themes that are appeared in the female authors' works throughout this long period. Using two computational tools, Stylo and Antconc, this paper reveals genre closeness and the most common themes that are appeared in twelve Dutch East Indies female novels which are collected from dbnl.org. Based on the cluster analysis, this paper divides the novels into four different clusters. More over the computational analysis also shows the three main themes; exploration, disadvantages of being a repressed group, and fighting against the oppressed. The use of extensive digital data in this research gives an alternative for literary researchers to find an alternative way of doing their research during this pandemic time, which makes the physical visit to the library limited. It also gives an alternative in the literature field to combine this discipline with computational tools.